Penerapan Metode Demonstrasi dalam Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Prakarya di MTs Negeri 2 Gunungkidul - Yeny Indrayanti (Jurnal Pendidikan Madrasah, 2020)
This research aims to improve students' learning outcomes in pre-work subjects of vegetable food processing by applying demonstration methods. The subject of this study is students of grade VII-B MTs Negeri 2 Gunungkidul year 2019/2020. The study used a class action method, carried out in two cycles. The results showed an increase in student learning outcomes in each cycle. Students' study results in cycle I averaged 67 with a complete 60%. In cycle II there was an increase in learning outcomes with an average score of 78 with a completeness of 80%. This research shows that the application of demonstration methods can improve the learning outcomes of students at MTs Negeri 2 Gunungkidul.